Metformin Alleviates Endometriosis and Potentiates Endometrial Receptivity via Decreasing VEGF and MMP9 and Increasing Leukemia Inhibitor Factor and HOXA10 - Cheng, Jing; Li, Chunyang; Ying, Yingfen; Lv, Jieqiang; Qu, Xianqin; McGowan, Eileen; Lin, Yiguang; Zhu, Xueqiong (Frontiers in Pharmacology, 2022)
Background: Endometriosis affects endometrial receptivity, a key factor for successful embryo implantation. Metformin treatment is associated with alleviating the symptoms of endometriosis; however the mechanism of metformin action is unclear. Neoangiogenesis plays an important role in the development and recurrence of endometriosis. In addition, the leukemia inhibitor factor (LIF) and HOXA10 genes are also distinguishing markers of endometriosis (decrease) and endometrial receptivity (increase).. This study investigated the therapeutic potentials of metformin and the underlying mechanism using an in vivo rat endometriosis model. Methods: Female Wistar albino mature rats with experimentally induced endometriosis were used in this study. Metformin was administered at doses of 100 mg/kg/d and 200 mg/kg/d. The volume of endometriotic implants was assessed. The protein and mRNA expression of the vascular endothelial growth factor (VEGF), matrix metalloproteinase-9 (MMP-9), the endometrial receptivity markers, leukemia inhibitor factor (LIF) and HOXA10, were measured in the endometrium of rats with endometriosis. Results: Metformin treatment significantly suppressed the growth of endometriotic implants. Further, the expression of VEGF and MMP-9 protein and mRNA in endometriotic implants were significantly reduced. Metformin also significantly upregulated LIF and HOXA10 expression in endometrium from rats with endometriosis. The inhibitory effect of metformin on the growth of endometriotic implants, VEGF and MMP-9, and upregulating effect on LIF and HOXA10, was optimal at a dose of 100mg/kg/d. Conclusions: Our in vivo data demonstrates that metformin treatment alleviates endometriosis and potentiates endometrial receptivity. The underlying mechanisms are associated with decreased expression of VEGF and MMP-9 genes and upregulation of the LIF and HOXA10 genes. The effect of metformin was optimal at 100mg/kg/d. These findings provide a potential alternative for women with endometriosis with the potential to increase fertility. Metformin is an approved drug by FDA for diabetes and this study may add another potential clinical use for metformin.